FORMULATION AND EVALUATION OF MUCOADHESIVE BUCCAL TABLETS CANTANING IVABRADINE HYDROCHLORIDE BY USING NATURAL POLYMERS - Premi, Manoj; Gupta, Manish Kumar; Phanindra, Bannaruvari (Journal of Biomedical and Pharmaceutical Research, 2019)
The buccal mucosa is moderately permeable, strong when match up with the other mucosal tissues and is more tolerant to potential allergens which have a compact affinity to unalterable irritation or harm. Mucoadhesive buccal drug delivery system offers a control release system; it entails the administration of required drug through the buccal mucosal membrane lining of the oral cavity. The Bioadhesive was resulting from the need to limit drugs at a definite site in the body. Significantly at the absorption site, enhance the degree of drug absorption is restricted by the residence time of the drug. The API, blend of excipients and drug were prepared at the ratio of 1:1, filled in closed vials and kept in accelerated environmental conditions (40°C/75% RH) for a period of 1 month. Excipients were employed here to assess the compatibility issue with the active ingredient. The possible drug and polymer interaction studies were assessed by using FTIR. Calibration curve of ivabradine HCl was constructed by dissolving pure drug of ivabradine HCl (100 mg) in 100 mL of phosphate buffer (pH 6.8) to give 1mg/mL concentration and designed as stock solution-1. The angle of repose was determined by fixed funnel method. The prepared mucoadhesive buccal tablets were estimated for post compression factors such as thickness, friability, drug content and hardness. The surface pH study was conducted on ivabradine HCl mucoadhesive buccal tablets, carried out to predict the comfort of the buccal formulation into the possibility of any side effects in buccal mucosa environment. F1 and F5 possessed the best results among all the formulations in terms of in vitro release of drug. However, F2 formulation shows highest mucoadhesive and swelling index than other formulation. Therefore, from the data, it may be concluded that F2 formulation might be considered as promising mucoadhesive buccal tablet formulation for a suitable sustained drug delivery system for ivabradine.Keywords: Ivabradine Hydrochloride, Buccal tablet, Mucoadhesive, Natural Polymers.